Examining the Impact of Airport Experience on Passenger Satisfaction and Green Image: A Case Study of Yogyakarta International Airport - Poerwadi, Yuniar Belly; Wiyadi, Wiyadi; Sholahuddin, Muhammad (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research investigates the influence of airport experience on passenger satisfaction and the perception of green image at Yogyakarta International Airport (YIA). The study utilizes the Experience Economy Theory, examining the roles of entertainment, education, aesthetics, and escapism in shaping passenger satisfaction and contributing to YIA’s green image. Data were collected from 327 passengers using a structured questionnaire based on a five-point Likert scale. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the relationships between the dimensions of the airport experience and their impact on passenger satisfaction and green image. The results indicate that educational and escapist experiences significantly enhance both satisfaction and green image, whereas entertainment and aesthetic dimensions have a less significant impact on the perception of YIA’s sustainability efforts. This study provides insights for airport managers on how to improve airport experiences and green initiatives to foster stronger passenger loyalty and environmental awareness.